(Invited) Electroplating of Bright Aluminum on the ABS Resin Substrate Covered with Cu Film in EmImCl-AlCl3 Ionic Liquid. (8th September 2020) - Ueda, Mikito
Abstract : To form bright and uniform Al electroplating film on Cu substrate, additive for electrolyte and support electrode were investigated in 1-ethyl-3-methylimidazolium chloride (EmImCl) and AlCl3 mixture ionic liquid. Al electroplating film from the ionic liquid containing the additive formed bright surface depend on rotation rate of ionic liquid electrolyte. By arranging the supporting electrodes, current concentration on the substrate was dispersed. An Al electroplated film having a uniform thickness was formed on the Cu substrate or ABS resin substrate covered with Cu plating. The electroplated film formed on the ABS substrate was anodized and showed pink, blue, and orange.